Life cycle assessment of geopolymer concrete: a comparative study - Meyrelles, Rafael; Calmon, João Luiz; Bello, Lukas Damazio; Medina, Taísa Menezes (Brazilian Journal of Production Engineering, 2024)
The construction industry is responsible for a considerable proportion of carbon dioxide emissions into the atmosphere. The production of concrete, which is the second most used material in the world, is responsible for most of the greenhouse gas emissions from buildings. This research aims to present solutions for reducing the carbon footprint of the construction industry. To obtain a diagnosis quantifying environmental impacts, it is necessary to use Life Cycle Assessment (LCA), which is a holistic methodology for environmental aspects and potential impacts, both direct and indirect, throughout life cycle of a product. The option to reduce the greenhouse gas emissions was the replacement of Conventional Concrete (CC) for Geopolymer Concrete (GC), which is made by completely replacing the binder, cement, with powdery materials rich in silica and alumina. Five different scenarios were evaluated, one city in each region of Brazil. The results of the LCA showed that GCs have great potential for reducing the carbon footprint, reducing up to 60% of global warming potential.
Keywords: Life Cycle Assessment; Geopolymer Concrete; sustainability; global warming